Investigating the Role of the Relative Humidity in the Co‐Occurrence of Temperature and Heat Stress Extremes in CMIP5 Projections. Issue 20 (30th October 2019) - Brouillet, Audrey; Joussaume, Sylvie
Abstract: Heat stress is expected to intensify, since temperatures are projected to increase during the 21st century. We investigate the assumed co‐occurrence of annual extremes of temperature and one heat stress metric and assess the effect of relative humidity variations on the heat stress changes. We show in CMIP5 simulations that both extremes tend to co‐occur in Europe and northern America, when the conditions are the hottest and the driest. However, extreme seasons occur later for heat stress than temperature by up to 2 months within the tropics. By 2100, models project a drying that hampers the increase in heat stress extremes. Within northeastern Africa, the slight projected wettening enhances the warming effect on the heat stress changes and induces the maximum heat stress intensification. Models are generally able to represent the phasing of both extremes compared to observations, with large uncertainties over regions experiencing the greatest future heat stress intensification. Plain Language Summary: Temperature and heat stress extremes are projected to intensify in the future. However, the occurrence and the changes in heat stress extremes also depend on humidity variations. We show that both extremes tend to co‐occur during the year in mid‐latitudes, but extremes of heat stress tend to occur later than temperature extremes in the tropics, when the relative humidity is annually higher. We also show in future climate simulations that the global projected drying that strengthens the increase in temperature extremes weakens the intensification of heat stress extremes. Nevertheless, this does not prevent risk for health, particularly in tropical areas. Key Points: Temperature and heat stress extremes tend to co‐occur in mid-latitudes but are time‐lagged in the tropics due to relative humidity The projected drying (wettening) weakens (strengthens) the heat stress intensification in midcontinental regions (northeastern Africa) Despite this weakening effect, future heat stress is projected to reach the most dangerous health thresholds in the tropics